Ontogenetic morphology of Tutorozetes incisirostris Ermilov, 2016, with remarks on juveniles of Punctoribatidae (Acari: Oribatida) - Bayartogtokh, Badamdorj; Ermilov, Sergey G. (Zootaxa, 2019)
The morphological ontogeny of most species of Punctoribatidae is still insufficient or unknown. Comparative characteristics of juveniles of Tutorozetes incisirostris are given for the first time in Tutorozetes based on material from southern Chile (Patagonia); and the major characteristics of juvenile instars of 15 punctoribatid species are presented, based on literature sources. The larva and nymphs of this species are generally similar to those of the other representatives of Punctoribatidae. Basic characteristics of juveniles are the body unpigmented, light yellowish or flesh-coloured with porose cuticle; gastronotic and anogenital regions folded; humeral organ absent; prodorsum stockier in larva than in nymphs and adult; gastronotic shield poorly sclerotized; prodorsal, gastronotic and ventral setae setiform, except clavate bothridial seta; larva with 12 pairs, nymphs with 15 pairs of gastronotic setae. We discuss the generic status of Tutorozetes and its possible synonymy with Minunthozetes.